Exploring English language learning and teaching in Malaysia - Normazidah Che Musa; Koo, Yew Lie; Hazita Azman (Penerbit UKM, 2012)
This paper presents a review of recent research that investigates the problem and the practice of English language teaching and learning in Malaysia. The aim of the paper is to identify the factors that contribute to low or limited English literacy achievement among Malaysian learners. A review of these studies indicates a general pattern of dissatisfaction among students, educators, policy makers and the public regarding the teaching and learning of the language (Razianna Abdul Rahman, 2005; Rosemala Ismail, 2008). In addition, studies focusing on English language proficiency among Malaysian university graduates also seem to resonate a feeling of uneasiness with the graduates’ level of English proficiency (Isarji Sarudin et al., 2008). This paper therefore discusses some of the key issues and competing discourses confronting English language learning in this country. It reflects on how the teaching of English is variously conceptualized in our classrooms, raising important questions about the positions of English literacy to Malaysian learners and the society in general.